2003
DOI: 10.1248/cpb.51.740
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the Plant Origin of Brazilian Propolis by the Observation of Honeybee Behavior and Phytochemical Analysis

Abstract: Propolis, a natural resinous substance collected by honeybees from buds and exudates of plants, has been considered to be used in the beehive as a protective barrier against their enemies. Recently propolis is extensively used in food and beverages to improve health and prevent diseases. 1)The composition of propolis depends on the place and time of collection. Much research and development has been implemented on propolis all over the world. Most of the recent studies are related to Brazilian propolis because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
31

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(191 citation statements)
references
References 8 publications
5
155
0
31
Order By: Relevance
“…Propolis form Europe and China had high flavonoid and phenolic contens (Bankova et al, 2000). On the other hand, propolis from Brazil showed high terpenoid and cumaric acid derivative (Kumazawa et al, 2003). Moreover, propolis extracts by maceration and sonication showed the same contents of flavonoid and flavones compounds (Marghitas et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis form Europe and China had high flavonoid and phenolic contens (Bankova et al, 2000). On the other hand, propolis from Brazil showed high terpenoid and cumaric acid derivative (Kumazawa et al, 2003). Moreover, propolis extracts by maceration and sonication showed the same contents of flavonoid and flavones compounds (Marghitas et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of propolis found around the world is derived from poplar buds; however, the most common type in Brazil, Brazilian green propolis from the southeastern part of the country, is derived from the buds of Baccharis dracunculifolia [3], and a recent our study reported that Brazilian red propolis from the northern part of the country is derived from Dalbergia ecastophyllum [4]. It appears highly likely that various types of propolis remain undiscovered around the world.…”
Section: Introductionmentioning
confidence: 90%
“…We have reported that Brazilian green propolis contains high levels of artepillin C (3,5-diprenyl-4-hydroxycinnamic acid, ARC) ( Figure 1) [3]. Although we and other investigators have reported that ARC can suppress tumor growth both in vitro and in vivo [5], the actual mechanisms of these effects are not yet fully understood.…”
Section: Biological Activitiesmentioning
confidence: 98%
“…They can be classified into two main groups: the Brazilian-type (Baccharis-type) and the European-type (poplar-type). The Brazilian-type propolis is rich in p-coumaric acid derivatives, such as artepillin C and (E)-3-prenyl 4-(dihydrocinnamoyl-oxy)-cinnamic acid (KumAzAwA et al, 2003), dihydrokaempferol, 4-hydroxy-3-prenylbenzoic acid, and plicatin B, and is found only in Brazil. While the European-type propolis is rich in flavonoids and phenolic acid esters, particularly pinocembrin, pinobanksin, galangin, chrysin, and caffeic acid phenetyl ester, as the major source of the propolis is bud exudates of the populus species and is collected not only in Europe but also in China and other countries (KumAzAwA et al, 2004).…”
Section: Hplc Analysis Of Eepsmentioning
confidence: 99%